COVID-19 and H1N1 pandemics’ impact on the financial performance of listed companies and sectors in Malaysia - Ahmad Zaki, Ahmad Izzat (2021)
This study investigates how pandemics affect listed companies and sectors in Malaysia. I provide empirical analysis on the financial impact of COVID-19 and H1N1, using Z”-Score as proxies for the financial performance of twelve sectors for the period of 2008-2020. My results suggest that all Malaysian listed companies are well above the Safe Zone minimum threshold. Then, the Technology sector was identified as the top performer over the study period. I find no evidence to counter that COVID-19 is more severe compared to the H1N1 pandemic in impacting the financial performance of listed companies. Finally, my study reveals differences in the performance of sectors in Malaysia.